Social Criticism after the Pandemic Era on the Visual of the Truck Body - Hardoyo, Adityo Baskoro (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out the narrative of social criticism contained in the back of the body truck. Trucks are a means of transport to carry various needs in massive quantities. Many truck owners decorate the tailgate with various visuals. Most of the graphics on the back of the truck are in the form of a beautiful woman, but one of the trucks that is used as the object of research this time displays a visual of social criticism. In the post-pandemic era, social criticism on the back of a truck became interesting because many driver who had pass over and over again in the streets would see it. The method used in this research is Bahasa Rupa Primadi Tabrani to study the visual style, color and typography on the tailgate. Impact From this research, it is hoped that new insights will be obtained regarding visual styles and visual messages on truck bodies after the pandemic era.